Full-length genome sequence of a dengue serotype 1 virus isolate from a traveler returning from Democratic Republic of Congo to Italy, July 2019. (March 2020) - Colavita, Francesca; Vairo, Francesco; Carletti, Fabrizio; Boccardo, Chiara; Ferraro, Federica; Iaiani, Giancarlo; Al Moghazi, Samir; Galardo, Gioacchino; Lalle, Eleonora; Selvaggi, Carla; Scognamiglio, Paola; Capobianchi, Maria Rosaria; et al.
Highlights: Dengue virus (DENV) is underreported in Democratic Republic of Congo (DRC). We report an imported acute case of primary dengue from DRC to Italy. Whole genome sequencing analysis confirmed the causative species to be DENV type 1. The strain identified is closely related to 2013 strains derived from China and Angola. Our finding raises awareness of DENV in DRC currently affected by the Ebola outbreak. Abstract: We report the full-genome sequence of a Dengue serotype-1 virus (DENV-1) isolated from a traveler returning in July 2019 to Italy from Democratic Republic of Congo (DRC), which is currently affected by Ebola and measles outbreaks. The sequence shows high similarity with two 2013 strains isolated in Angola and China.